Comparison of Peritonitis Relapse Incidence in End-Stage Renal Disease Patients with Peritoneal Dialysis According to the Culture Results - Mirza Zaka Pratama; Achmad Rifa'i; Atma Gunawan; Nadina Mustamsir (Universitas Brawijaya, 2022)
Background: Peritoneal dialysis (PD) is one of the modalities of renal replacement therapy (RRT) in end-stage renal disease (ESRD). One of the complications that are often found in the use of PD is peritonitis. Presence of the culture from the peritoneal fluid was known to be associated with the incidence of peritonitis relapse among ESRD patients with PD. Aim: Comparing the incidence of relapse in patients with continuous ambulatory peritoneal dialysis (CAPD) with culture-negative and culture-positive in RSUD Dr. Saiful Anwar Malang. Methods: This study measured the incidence of relapse after administration of CAPD peritonitis therapy. Descriptive data are presented in percentages, and numerical data is presented in Mean ± SD. The analysis test was carried out using the Mann-Whitney with p<0.05, significant. Results: According to the culture results, it was found that 25.4% (18 of 71 PD peritonitis cultures) were culture-negative in patients with CAPD peritonitis. This result is slightly higher than the ISPD recommendation, with 20% culture-negative results. There were 3 out of 53 relapses in culture-positive subjects and 1 in 18 relapses in culture-negative subjects. There was no significant difference in the two groups, with an OR of 0.721 in the culture-positive group lead the culture-positive tended to experience no relapse by 0.721 times less than the patient with culture-negative. Conclusion: In peritoneal dialysis peritonitis, there was no significant difference in the incidence of relapse in the positive and culture-negatives.